Natural killer cells-related immune traits and amyotrophic lateral sclerosis: A Mendelian randomization study - Gong, Zhenxiang; Liu, Yang; Ding, Fengfei; Ba, Li; Zhang, Min (Frontiers in Neuroscience, 2022)
Background: Observational studies have suggested that peripheral immune disorders are associated with amyotrophic lateral sclerosis (ALS). Previous studies predominantly focused on changes in adaptive immunity. However, emerging evidence showed natural killer (NK) cells, an essential component of innate immunity, were involved in the degeneration of motor neurons. However, the causal relationship between dysregulated NK cells-related immune traits and ALS remains unclear. Objective: This study aimed to explore the causal relationship between NK cells-related immune traits and the risk of ALS. Methods: Single nucleotide polymorphisms (SNPs) significantly associated with NK cells-related immune traits were selected as instrumental variables to estimate their causal effects on ALS. SNPs from a genome-wide association study (GWAS) on NK cells-related immune traits were used as exposure instruments, including an absolute NK-cells count, absolute HLA-DR+ NK-cells count, NK cells/lymphocytes, NK cells/CD3– lymphocytes, HLA DR+ NK cells/NK cells, HLA DR+ NK cells/CD3– lymphocytes, and the median fluorescence intensities of CD16–CD56+ on NK cells and HLA-DR+ NK cells. Summary-level GWAS statistics of ALS were used as the outcome data. Exposure and outcome data were analyzed using the two-sample Mendelian randomization (MR) method. Results: Each one standard deviation increase in the expression levels of CD16–CD56+ on NK cells and HLA-DR+ NK cells were associated with a lower risk of ALS in both the MR-Egger and inverse variance weighted methods (P < 0.05). The results proved robust under all sensitivity analyses. Neither instrumental outliers nor heterogeneity were detected. Conclusions: Our results suggest that higher expression levels of CD16–CD56+ on NK cells and HLA-DR+ NK cells are associated with a lower risk of ALS.